Towards an Asian economic community : vision of a new Asia - Kumar, Nagesh, 1958-; Research and Information System for the Non-aligned and Other Developing Countries; Institute of Southeast Asian Studies; International Conference on'Building a New Asia: Towards Asian Economic Community' (2003 : New Delhi, India) (Singapore : Institute of Southeast Asian Studies, 2004)
Contributed papers presented at the International Conference on'Building a New Asia: Towards Asian Economic Community,' on 10-11 March, 2003, at New Delhi
Includes bibliographical references
Keywords: Asia -- Economic integration -- Congresses; Asia -- Economic policy -- 20th century -- Congresses